Detachment faulting in a bivergent core complex constrained by fault gouge dating and low-temperature thermochronology. (October 2019) - Heineke, Caroline; Hetzel, Ralf; Nilius, Nils-Peter; Zwingmann, Horst; Todd, Andrew; Mulch, Andreas; Wölfler, Andreas; Glotzbach, Christoph; Akal, Cüneyt; Dunkl, István; Raven, Mark; Hampel, Andrea
Abstract: The central Menderes Massif in western Turkey is a bivergent metamorphic core complex characterised by two detachment faults that operated with opposite sense of shear. Here, we present K–Ar ages and hydrogen isotope data for fault gouge as well as fission track and (U–Th)/He ages for apatite and zircon from bedrock samples to constrain the timing of detachment faulting. Comparison of the K–Ar ages and low-temperature thermochronologic ages indicates brittle faulting at temperatures between ~240 and ~70 °C. At the western termination of the Gediz detachment, K–Ar ages between ~12 and ~5 Ma suggest rather continuous faulting since the mid-Miocene; a Pliocene phase of rapid slip is mainly recorded in the eastern part of this detachment. In contrast, K–Ar ages from the Büyük Menderes detachment cluster at 22–16 and 9–3 Ma and provide evidence for two phases of faulting, which is in accordance with new and published low-temperature thermochronologic data. Hydrogen isotope ratios of −76 to −115‰ indicate infiltration of meteoric water during detachment faulting and gouge formation. The youngest K–Ar ages and cooling histories for hanging and footwall rocks imply that the activity of both detachments ended ~3 Ma ago when the currently active grabens were established. Highlights: K–Ar ages of fault gouge record detachment faulting in a bivergent core complex. Two detachment faults were active diachronously between ~22 Ma and ~3 Ma. The Büyük Menderes detachment experienced two phases of faulting since ~22 Ma. The Gediz detachment was active continuously from mid-Miocene to late Pliocene.